1984
DOI: 10.1002/ajmg.1320170108
|View full text |Cite
|
Sign up to set email alerts
|

Restudy of the original marker X family

Abstract: Restudy of the original marker-X family confirmed recent observations that this XLMR disorder is associated with large testes and slightly abnormal ears. However, other aspects of the phenotype were variable and a distinct facies was not evident. Significant differences in marker-X frequency between two laboratories processing the same samples were observed. Possibly, the combination of more cells and a longer culture time in one laboratory led to a greater depletion of critical nutrients and a higher frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

1984
1984
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 2 publications
0
15
0
4
Order By: Relevance
“…Peripheral blood lymphocytes were cultured in medium 199 with 2% fetal calf serum as previously described (Lubs, Watson, Breg, & Lujan, 1984). Not all residents of the institution were screened for the syndrome.…”
Section: Subjectsmentioning
confidence: 99%
“…Peripheral blood lymphocytes were cultured in medium 199 with 2% fetal calf serum as previously described (Lubs, Watson, Breg, & Lujan, 1984). Not all residents of the institution were screened for the syndrome.…”
Section: Subjectsmentioning
confidence: 99%
“…Thus, the identity between the fragile X and Martin-Bell syndromes was formally established. Likewise, Lubs did a follow-up study on the family of his patients and found that they had the Martin-Bell syndrome with macroorchidism [Lubs et al, 1984].…”
Section: The Fragile Xmentioning
confidence: 96%
“…A prominent example of this type of shifting diagnostic criteria is Fragile-X syndrome, which was originally described as a non-syndromic form of ID. 62,63 Furthermore, some mutations can give rise to both non-syndromic and syndromic ID, depending on their nature or location within the gene (for examples see e.g., Ropers and Hamel 64 ). One line of investigation could examine correlations between different mutations in ZC3H14 and the severity of ID or specific accompanying clinical features.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%